Usefulness of serotoninergic challenge with oral citalopram - Mattos,Paulo (2006)
OBJECTIVE: Challenge tests designed to evaluate serotoninergic pathways have widely used intravenous citalopram. Oral citalopram has also been used, but unsatisfactory results were obtained with a dose of 20 mg. The objective of this study was to determine whether a higher oral dose would reproduce similar to those described for intravenous administration. To that end, we evaluated cortisol, growth hormone and prolactin levels. METHOD: Eight healthy male volunteers were evaluated in a randomized crossover challenge test with 40 mg of oral citalopram or placebo. RESULTS: Cortisol levels increased at 2-4h after the oral citalopram intake, with a small amplitude peak occurring in two-thirds of the subjects. Levels of prolactin and growth hormone remained unchanged throughout the study. CONCLUSION: The use of oral citalopram might present an alternative in serotoninergic challenge tests, but higher doses are required.